The Position of Children's Characters in Children's Animation Postcolonialism Studies - Siti Zahrok; Encik Savira Isnah; Marsudi Marsudi; Enie Hendrajati; Edy Subali; Wahyudin Wahyudin (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2024)
Children's literature has now begun to shift to digital media, known as children’s animation. Instead of children's literature being created for children, these works are written, edited and distributed by adults. This shows that adults (parents) have full power over the work that children will consume. Colonialism theory then questions what it means to write for children. This research appears with the real assumption of where the child is positioned in children’s cyber literature. The postcolonial approach is used to verify this assumption. The results show that children are treated as objects, a means to endure real problems faced by adults. It appears that writing for children in addition to exploring is also stuffing and imposing the will for the needs of adults: guiding children, training children through the process of reaching civilization which is again the power of adults to define it.